Pemikiran Ushul Fiqih Ibnu Qudamah : Kajian Atas Beberapa Masalah Fiqih Dalam Kitab Al-Kafi Fi Fiqh Al-Imam Ahmad Bin Hanbal - Ihsan Nul Hakim (AL-ISTINBATH : Jurnal Hukum Islam, 2016)
This study has conducted to analyze the thought of Ibn Qudamah about “ushul fiqih” through some “fiqhiyah” problems contained in the book “al-Kafi Fi Fiqh al-Imam Ahmad bin Hanbal”. Ibn Qudamah is a famous theologian in the sect of Ahmad ibn Hanbal. However, there are doubts whether he developed a framework or his own method or influenced by the methods of his teacher. The data presented in this study came from primary source, the book titled “al-Kafi Fi Fiqh al-Imam Ahmad bin Hanbal”, Ihsan Nul Hakim: Pemikiran Ushul Fiqih Ibnu Qudamah | 82 by giving a brief introduction about the discussed themes of jurisprudence and then introducing the opinions of law of jurists (especially the four sects of islamic fiqh) on aspects of the differences and the reasons and basis of their opinion, finally presenting“ushul-fiqih” thought of Ibn Qudaamah. The issues or themes broadly divided into four areas, they are religious jurisprudence, wedding jurisprudence, commerce jurisprudence and felony jurisprudence. This study has concluded that the opinion of Ibn Qudamah jurisprudence generally in line with his teacher’s jurisprudence, Ahmad ibn Hanbal, as well as in the field of “ushul-fiqh” jurisprudence, Ibn Qudamah used the basics, such as The Qur'an, Hadith, judgment of prophet’s friends, “Qiyas” and “maslahah mursalah”.